Jigsaw learning model in increasing interest and learning of automotive electrical systems - Cecep Ardian; Subagyo Subagyo; Arif Bintoro Johan (Jurnal Taman Vokasi, 2019)
The purpose of this study was to determine the increase in interest in learningvand learning outcomes Automotive subjects Jigsaw cooperative learning model. This research is a class act. The data collection technique using observation, tests and questionnaires. The validity of the instrument in this study using the content validity using expert judgment. Data were analyzed using quantitative analysis techniques. The results  showed  that  the  application  of  cooperative  learning  model  Jigsaw  on  the subjects of automotive electrical systems can increase interest and student learning outcomes in class XI SMK (Taman Karya) Tamansiswa Jetis Yogyakarta. Increased student  interest  in  the  first  cycle  an  average  of  59.04  (low)  increased  to  73.96 (currently) in the second cycle and increased again to 76.80 (high) in the third cycle. It can be concluded that Jigsaw cooperative learning model can improve learning outcomes interest and automotive electrical systems in class XI student of SMK (Taman Karya) Tamansiswa Jetis Yogyakarta.